2020
DOI: 10.7150/ijbs.46822
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-216a-5p inhibits tumorigenesis in Pancreatic Cancer by targeting TPT1/mTORC1 and is mediated by LINC01133

Abstract: MiR-216a-5p has opposite effects on tumorigenesis and progression in the context of different tumors, acting as either a tumor suppressor or an oncogene. However, the expression and function of miR-216a-5p in pancreatic cancer (PC) is not well characterized. In this study, we found miR-216a-5p was significantly downregulated in PC tissues and cell lines, which showed a negative correlation with peripancreatic lymph, perineural invasion and TNM stage of PCs patients. We made use of functional assays to reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…LincRNAs interact with proteins, miRNAs, and other molecules to exert their functions 35 . Previous studies suggested that LINC01133 sponges miR‐4784 and miR‐205 to counter miRNA‐mediated gene silencing in cervical cancer and gastric cancer, respectively 36,37 . Our miR‐seq and bioinformatics analyses revealed that LINC01133 sponges miR‐199a‐5p in HCC.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…LincRNAs interact with proteins, miRNAs, and other molecules to exert their functions 35 . Previous studies suggested that LINC01133 sponges miR‐4784 and miR‐205 to counter miRNA‐mediated gene silencing in cervical cancer and gastric cancer, respectively 36,37 . Our miR‐seq and bioinformatics analyses revealed that LINC01133 sponges miR‐199a‐5p in HCC.…”
Section: Discussionmentioning
confidence: 63%
“…35 Previous studies suggested that LINC01133 sponges miR-4784 and miR-205 to counter miRNA-mediated gene silencing in cervical cancer and gastric cancer, respectively. 36,37 Our miR-seq and bioinformatics analyses revealed that LINC01133 sponges miR-199a-5p in HCC. We also predicted on the basis of bioinformatic analysis that LINC01133 interacts with miR-501-5p, but qRT-PCR revealed that LINC01133 did not affect the expression of miR-501-5p in HCC cells.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, no research related to MIR600HG and AP004608.1 has been published so far and there are only a few studies focusing on the mechanism of LINC00857 in cancers. As for LINC01133, Zhang et al 24 have reported a LINC01133/miR-216a-5p/TPT1/mTORC1 ceRNA axis that regulated tumorigenesis of PAAD. We hoped to further complement the in-depth mechanism experiments for all of these potential lncRNAs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…LincRNAs interact with proteins, miRNAs, and other molecules to exert their functions [32]. Previous studies suggested that LINC01133 sponges miR-4784 and miR-205 to counter microRNA-mediated gene silencing in cervical cancer and gastric cancer, respectively [33,34]. We revealed that LINC01133 is a sponge of miR-199a-5p in HCC through miR-seq and bioinformatics analyses.…”
Section: Discussionmentioning
confidence: 74%